(untitled) (project baikal, 2023)
The news section announces this year’s winners of the UIA Triennial Prizes, the UIA Friendly and Inclusive Spaces Awards, the Next Generation of Stroke Rehabilitation Centres international student ideas competition and the DNA Paris Design Awards. It also provides information on the designation of Barcelona as the World Capital of Architecture for 2026.